Allied Patriotic Societies records - Allied Patriotic Societies
Documents proclaiming Law and Order Day in twenty states, Flag Day proclamations by governors, and other papers relating to the American flag, including one by President Coolidge.
Collection material in English.
Keywords: Coolidge, Calvin, -- 1872-1933.; Flag Day; Flags -- United States; Law and Order Day; Patriotic societies